KOMUNIKASI PARTISIPATIF WARGA PADA BENGKULU REGIONAL DEVELOPMENT PROJECT (KASUS DI DESA PONDOK KUBANG KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH) - Mulyasari, Gita (Jurnal AGRISEP, 2010)
The successful  of Bengkulu Regional Deoelopmeni   Project  was very determined    by  the society participation   in  all of the project activities. Without their participation,   those activities would not  be done as  the expectation.   In  order to  optimize the society's participation  in the development  project  (BRDP),  a good participative  communication   was needed to create a feedback  between the people involved in BRDP and the society. This research is aimed to analyze:  a) participating  on communication   in BRDP process,  b) the factors  influenced  the participation  between  the society and facilitator  in BRDP activities. The community participatory  communication   in the planning stage had a real connection with ability.  The community participatory  communication  in the stage of process was very connected with the capability changer too. The members of UPKD had given chances to ask questions,  opinions,  and suggestions   connected  with BRDP activities in Pondok  Kubang village, but the low of education,  experience, and financial capital of the society resulted  in their low participation  in BRD P activities. The low capability also reduced their motivation to participate.  The community  participatory  communication  in the stage of evaluation  had a real relation  with the honesty  changer.  In this stage, the community expected  the honesty UPKD and  transparency   in  case "who" has to get the right to get  the fund.    The community's dissatisfaction   toward the unhonestg UPKD member  in case of the facility development  projects  in Pondok  Kubang  village  has reduced participative  communication between the UPKD members and the communitf.